Polymeric hydrogel nanoparticles in drug delivery and bioprinting technologies: a review - Prasanta Kumar Ghosh (MGM Journal of Medical Sciences)
Multiple kinds of hydrogel polymers, natural and synthetic, are known. Self-assembly and aggregation are their inherent properties. The diverse applications of hydrogel polymers, encompassing natural and synthetic varieties known for their water-swelling capabilities and biocompatibility, have been explored and summarized. Hydrogels are pivotal in medicine, particularly in drug delivery systems, and emerging three-dimensional (3D) bioprinting technologies. Integrating nanoparticles into hydrogels enhances their functionality for targeted drug release and as components of bioinks used in bioprinting aimed at priming and replicating tissue and organ structures. Natural hydrogel polymers are favored for their biocompatibility characteristics in bioinks, while synthetic polymers and nanoparticles contribute to stronger mechanical properties and increased versatility. This study highlights the importance of the nanoparticle-based hydrogel polymer-entrapped drug substances for efficient use in tissue-specific delivery systems. It emphasizes the critical role of bioink development in advancing synthetic organ fabrication via the 3D bioprinting technology.